2018
DOI: 10.3390/app8050743
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Behaviors of Prisms Made of Demolished Concrete Lumps and Fresh Concrete

Abstract: Directly adopting coarsely crushed demolished concrete lumps (DCLs) with pouring concrete (referred to as fresh concrete, FC) in new structural members has been demonstrated to be more efficient and environmental than the traditional approach of recycling waste concrete as coarse aggregate particles. In this study, 45 prisms made of FC and DCLs were tested under axial compressive loading up to failure. The varied parameters included the dimensions of the prisms, the replacement ratio of DCLs, and the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Extensive research has been conducted by Wu’s group (Wu et al, 2013, 2014, 2015, 2016, 2018a, 2018b, 2018c, 2019; Wu and Jin, 2019; Zhao et al, 2016) in the previous decade, demonstrating the effectiveness of this recycling method. The Wu’s group research is mainly focused on compound concrete–filled steel tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted by Wu’s group (Wu et al, 2013, 2014, 2015, 2016, 2018a, 2018b, 2018c, 2019; Wu and Jin, 2019; Zhao et al, 2016) in the previous decade, demonstrating the effectiveness of this recycling method. The Wu’s group research is mainly focused on compound concrete–filled steel tubes.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, lower hydration heat is released during recycled lump concrete production. A series of studies showed that recycled lump concrete has comparable mechanical properties such as compressive strength and elastic modulus [19][20][21][22], tensile strength [23] and durability [24,25] with OPC concrete. The structural members, made of recycled lump concrete, exhibit similar flexural and shear behavior [26,27], compression behavior [28], fire resistance [29], seismic performance [30] and long-term creep behavior [31] as the benchmark members made with fresh OPC concrete alone.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of properties of sustainable construction materials, "green" concrete materials [20][21][22][23], composite materials [24,25], recycled materials [26][27][28], soil/rock materials [29,30] and other novel environmentally friendly construction materials [31,32] are reported in this issue. The investigations of the behaviours of structures constructed with different materials include demolished concrete structures [33,34], high-performance concrete structures [35], steel structures [36,37], steel-concrete composite structures [38,39] and fiber-reinforced polymer (FRP)-concrete hybrid structures [40][41][42][43]. In addition, seismic behaviour and the interaction behaviour between superstructure and substructure are discussed in two papers [44,45].…”
mentioning
confidence: 99%